SEROPREVALENCIA DE Toxoplasma gondii EN VICUÑAS DE PUNO - Pastor V., José (2003)
The objective of this study was to determine the seroprevalence of Toxoplasma gondii in Vicuñas of Puno. For this purpose, 101 mature vicuña were blood sampled in November 2000. The Indirect Hemoaglutination Test for the detection of antibodies was used. The seroprevalence was 14.9 ± 86% (15/101). The study revealed a low seroprevalence as compared with local findings in alpacas and llamas.